İflas Erteleme Talebinde Bulunan Grup Şirketlerinde “Kefalet” Çelişkisi - Kaplanhan, Fatih (Ankara Barosu, 2018)
“İflas erteleme” uygulaması Türk hukukunda ilk kez 6762 sayılı Türk Ticaret Kanunu’nun 324. maddesinde düzenlenmiştir. Daha sonra ise yeni TTK’nın 377. maddesinde iflasın ertelenmesi ile ilgili düzenlemeler yapılmıştır. Bu maddede özetle; şirketin mali durumunun bozulması halinde mahkemeye iyileştirme projesi sunularak iflasın ertelenmesi istenebilir. Uygulamada; ortakları aynı veya büyük oranda benzer olan (grup) şirketleri her ne kadar ayrı tüzel kişilikler olsa da birbirlerine gerek ortakları bakımından gerekse kefalet, taşeronluk vs ilişkileri bakımından bir birlerine çok sıkı bağlı olabilmektedir. Bu sebeple grup şirketlerinden herhangi birisinin mali durumunun bozulması veya aktiflerinin pasiflerini karşılayamaması durumunda grup şirketlerinin de mali durumu bozulabilmektedir. Bu durumda ayrı tüzel kişilikler olarak bu grup şirketlerinin her biri İflas Erteleme talebinde bulunmaktadır. Grup şirketlerinin açtıkları iflas erteleme davalarında, şirketlerin birbirlerine olan kefaletlerinin yorumlanması farklılık arz etmektedir. Henüz mevzuat ve teamül oluşmadığı için farklı yorumlar farklı uygulamalara sebep olmakta bu da telafisi mümkün olmayan hatalara neden olmaktadır. Bu çalışmada da iflasın ertelenmesi başvurusunda bulunan grup şirketlerinde yaşanan; kefalet yorumu sorununa değinilerek çözüm önerileri sunulacaktır.

The practice of “Bankruptcy Postponing” in Turkish law first came about with the provision in Article 324 of the Turkish Commercial Code numbered 6762. The practice of “Bankruptcy Postponing” in Turkish law first came about with the provision in Article 324 of the Turkish Commercial Code numbered 6762. Later, regulations were made regarding the postponing of bankruptcy in Article 377 of the new Turkish Commercial Code. In summary of this Article: in the event that the financial situation of the company deteriorates, postponement of bankruptcy may be requested upon presenting a project of improvement to the court. In practice: group companies whose shareholders are the same or very similar, even though they are separate legal entities, can be tight-knit in terms of shareholders, guarantee, subcontracting etc. relations. For this reason, the financial situation of the group companies may deteriorate in circumstances where any one of the companies’ financial situation deteriorates or where the assets of the companies do not meet the liabilities. In this case, every one of the group companies as a separate legal entity make a request for postponement of bankruptcy. In lawsuits filed by group companies for postponement of bankruptcy, the interpretation of the companies’ suretyship as regards to each other will differ. As there is lack of legislation and practice, different interpretations lead to different implementation thus leading to errors with no remedies. The problem of guarantee interpretation as regards to group companies who haverequested postponement of bankruptcy will be addressed and solution suggestions will be given in this study
CONTR ADICTION OF “GUAR ANTEE” AS REGARDS TO GROUP COMPANIES THAT HAVE MADE A REQUEST FOR BANKRUPTCY POSTPONING
* Fatih Kaplanhan. İstanbul Sabahattin Zaim Üniversitesi, İşletme ve Yönetim Bilimleri Fakültesi, Uluslararası Ticaret ve Finans Bölümü Öğretim Üyesi, İstanbul, Türkiye. orcid.org/0000-0003-4138-1148
Keywords: İflasın ertelenmesi; Grup şirketler; Kefalet; İhtiyari/mecburi dava arkadaşlığı; Bankruptcy postponing; Group company; Guarantee; Facultative/obligatory joinder of parties